To Blanch an Ethiop: Motifs of Blackness in The Tempest and Ben Jonson’s Masque of Blackness - Christina Lynn Gutierrez-Dennehy (Humanities)
In the period between 2021 and 2022 immediately following the COVID-19 lockdowns, there were 37 professional or academic productions of The Tempest in the United States. The play was by far the most produced of Shakespeare’s works in this timespan, and those 37 productions represent a 280% increase compared to 2019, in which there were 13 such productions. Considering The Tempest’s hyper-popularity within the context of the Black Lives Matter Movement and the birth of We See You White American Theatre’s calls for reform in 2020, this paper seeks to understand anew the way in which Shakespeare constructs blackness in the play. Indeed for all of its beauty and magic, The Tempest stages a violent anti-blackness in its treatment of Caliban. In particular, I argue an unexplored connection between The Tempest and Ben Jonson’s 1605 court masque, The Masque of Blackness, itself an exploration of the construction of race for a particular early modern audience. My exploration here began as a partial answer to a question posed by Robin Alfriend Kello: “how do you balance [an] attraction to the richness of Shakespearian verse against these layered histories of racial violence and exclusion?” A deeper understanding of Shakespeare’s version of blackness may grant insights into areas of intervention for those theaters reaching for The Tempest amidst national calls for anti-racist theatrical work.